Hospitalization Rates and Causes Among Persons With HIV in the United States and Canada, 2005–2015. (21st October 2020) - Davy-Mendez, Thibaut; Napravnik, Sonia; Hogan, Brenna C; Althoff, Keri N; Gebo, Kelly A; Moore, Richard D; Horberg, Michael A; Silverberg, Michael J; Gill, M John; Crane, Heidi M; Marconi, Vincent C; Bosch, Ronald J; et al.
Abstract: Background: To assess the possible impact of antiretroviral therapy improvements, aging, and comorbidities, we examined trends in all-cause and cause-specific hospitalization rates among persons with HIV (PWH) from 2005 to 2015. Methods: In 6 clinical cohorts, we followed PWH in care (≥1 outpatient CD4 count or HIV load [VL] every 12 months) and categorized ICD codes of primary discharge diagnoses using modified Clinical Classifications Software. Poisson regression estimated hospitalization rate ratios for calendar time trends, adjusted for demographics, HIV risk factor, and annually updated age, CD4, and VL. Results: Among 28 057 patients (125 724 person-years), from 2005 to 2015, the median CD4 increased from 389 to 580 cells/µL and virologic suppression from 55% to 85% of patients. Unadjusted all-cause hospitalization rates decreased from 22.3 per 100 person-years in 2005 (95% confidence interval [CI], 20.6–24.1) to 13.0 in 2015 (95% CI, 12.2–14.0). Unadjusted rates decreased for almost all diagnostic categories. Adjusted rates decreased for all-cause, cardiovascular, and AIDS-defining conditions, increased for non-AIDS–defining infection, and were stable for most other categories. Conclusions: Among PWH with increasing CD4 counts and viral suppression, unadjusted hospitalization rates decreased for all-cause and most cause-specific hospitalizations, despite the potential effects of aging, comorbidities, and cumulative exposure to HIV and antiretrovirals. Abstract : From 2005 to 2015, in 6 US and Canadian clinical cohorts of persons with HIV with increasing age, viral suppression, and CD4 counts, unadjusted hospitalization rates decreased overall and for most causes.